Antimicrobial therapy approaches in the mastitis control driven by one health insights - de Souza, Miliane Moreira Soares; Dubenczuk, Felipe Carlos; Melo, Dayanne Araújo; Holmström, Thérèsse Camille Nascimento; Mendes, Marcela Barlette; Reinoso, Elina Beatriz; Coelho, Shana Mattos Oliveira; Coelho, Irene Silva (Brazilian Journal of Veterinary Medicine, 2024)
The use of antimicrobials in the dairy production environment for mastitis control must take etiology, clinical signs, economic impacts, and regulatory frameworks into consideration. The objective of the present review is to highlight important aspects of the dynamics of antimicrobial use in dairy production and the potential impacts on the main pathogens circulating in this environment, considering the parameters set by the World Health Organization (WHO) regarding the priority of monitoring as well as control strategies for these agents, such as the methicillin-resistant Staphylococcus and the beta-lactamase-producing Escherichia coli. Understanding the animal-environment-pathogen triad is crucial for establishing control measures and preventing the spread of bacterial resistance. Implementing mastitis prevention and control measures in dairy farms, considering process flow and personnel qualification, enables a reduction in antimicrobial usage and contributes to prevent the spread of resistant bacterial agents in the dairy production environment, minimizing the relapses and the chronicity of the infectious process.